Study on the therapeutic effect of eggshell membrane on osteoarthritis in rats - Mingming Pan; Yanhua Shen; Jiayu Wu; Chaonan Liu; Meihong Zhu; Zhengyu Zhou (PLoS ONE, 2026)
This study aimed to investigate the therapeutic effects of ELASEM ® Flex and ELASEM ® ProFlex, two eggshell membrane (EM) products, on sodium iodoacetate (MIA)-induced osteoarthritis (OA) in rats. An OA model was established by a single intra-articular injection of MIA into the knee joint. After modeling, rats were administered diclofenac sodium, ELASEM ® Flex, and ELASEM ® ProFlex by gavage daily for 4 consecutive weeks. During the experiment, food intake, water intake, body weight, and plantar mechanical pain threshold (MPT) of rats were measured weekly. Serum levels of TNF-α, COX-2, IL-1β, and CTX-II were assessed at weeks 2 and 4. After 4 weeks, knee joints were harvested for histopathological examination (HE staining and Safranin-O fast green staining). Results indicated that knee joints of OA rats showed significant swelling, which was alleviated to varying degrees in all treatment groups. Both ELASEM ® Flex and ELASEM ® ProFlex significantly increased the MPT (P < 0.05) and demonstrated sustained analgesic effects. These treatments also significantly reduced the serum levels of IL-1β, COX-2, TNF-α, and CTX-II at weeks 2 and 4 (P < 0.05). Histopathological analysis revealed that both EM preparations markedly alleviated arthritis symptoms, improved cartilage structure, promoted chondrocyte proliferation, enhanced staining of chondrocytes and cartilage matrix, and resulted in significantly lower Mankin's scores compared to the OA model group (P < 0.05). These results indicate that ELASEM ® Flex and ELASEM ® ProFlex can exert preventive and reparative effects on knee OA in rats by alleviating arthritis pain, inhibiting inflammatory factor expression, reducing type II collagen degradation, and promoting chondrocyte proliferation.